Optimising powdered activated carbon dosing procedures for removal of natural organic matter - Carroll, Stuart (Cranfield University, 2009)
The performance of three different types of PAC was analysed for the efficiency at which they remove natural organic matter (NOM) from untreated (raw) water, with the objective of ultimately reducing disinfection bi-product (DBP) formation. The treatment of raw water by PAC was also examined in conjunction with the addition of iron salts in the form of ferric sulphate, for coagulation and flocculation of NOM. The optimum dosing of PAC was achieved at pH 3 and at a dose of around 20mgl- 1 which gave 32.7% removal. Coagulation could be seen to give 88% removal and when used together PAC and coagulant gave between 93.6% and 97% removal of NOM. The dosing sequence of PAC and coagulant was investigated whereby it was found that optimum removal was achieved by dosing PAC prior to dosing coagulant, although if the delay between dosing PAC and coagulant was more than 30 seconds it was found to impair NOM removal and increase turbidity. Scale up trials of the dosing strategy were implemented at both Ewden water treatment works, in Yorkshire, and at the Pilot Hall in Cranfield University. The greatest reduction in DBP formation could be seen using Norit SA Super and coagulation. Dosing this activated carbon at 20mgl- 1 resulted in a decrease of DBP formation by 86% in raw water and by 78.7% using coagulation alone. Dosing PAC before coagulant produced the lowest levels of DBPs, which were 27.2μgl-1. This is much lower than the 80μgl-1 limit to which water treatment works must adhere.